ลักษณะของผู้ป่วยซิฟิลิสที่มีการติดเชื้อเอชไอวีและไม่มีการติดเชื้อเอชไอวีในโรงพยาบาลจุฬาลงกรณ์ระหว่างปี พ.ศ. 2544-2549 - ศิริวรรณ แซ่อึ้ง (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
Syphilis is a sexually transmitted disease which increases the risk of infection and transmission of HIV. Clinical manifestation of syphilis is more severe in HIV-infected patients. Currently, there has been no study about the characteristics of syphilis patients with and without HIV infection in Thailand. The objectives of this descriptive study were to determine and compare the characteristics of syphilis patients with and without HIV infection in King Chulalongkorn Memorial Hospital. Data of syphilis patients in King Chulalongkorn Memorial Hospital during past 5 years were collected retrospectively from 1st June 2001-31st May 2006 There were totally 385 syphilis patients, whose data could be retrieved and 325 (84.4%) were tested for HIV infection. Among these, one-hundred and eight patients were HIV infected. We found that 53.3% of patients were female. The mean age was 39.6±14.0 years and 65.2% were married. Most of the patients were employees (51.9%) and 89.5% were infected via heterosexual transmission. There were 290 syphilis patients (89.2%) without history of past treatment. Most of the patients had latent syphilis (81.6%) and 42.9% of VDRL testing were reactive with titer 1:1-1:8. Only 8.6% had lumbar puncture of which 8.0% were reactive for VDRL, We found that 57.2% of patients received medical treatment of which 73.5% were treated with benzathine penicillin G. Among patients who received treatment 67.8% were given standard treatment for sexually transmitted diseases according to guidelines of Department of Diseases Control, Ministry of Public Health. We found that 93.4% of patients were not informed to notify their partners for seeking care and 69.3% did not follow up. There were 65.2% of patients who came to follow up according to the physician’s appointment. There were statistically significant differences between syphilis patients with and without HIV infection (p<0.05) according to age, sex, status, route of acquisition, clinical manifestation, result of VDRL test and follow up. Syphilis patients with HIV infection are more likely to be male, younger, single, homosexual/bisexual. They were also more likely to have secondary syphilis and come to follow up after treatment more than syphilis patients without HIV infection. In conclusion, all syphilis patients should be offered HIV testing particularly homosexual/bisexual clients and patients with secondary syphilis. Management of syphilis patients in King Chulalongkorn Memorial Hospital should be revised according to standard treatment guidelines of sexually transmitted diseases including emphasis on patients follow up and partner notification.